Direct Monitoring of γ‐Glutamyl Transpeptidase Activity In Vivo Using a Hyperpolarized 13C‐Labeled Molecular Probe. Issue 36 (2nd August 2016) - Nishihara, Tatsuya; Yoshihara, Hikari A. I.; Nonaka, Hiroshi; Takakusagi, Yoichi; Hyodo, Fuminori; Ichikawa, Kazuhiro; Can, Emine; Bastiaansen, Jessica A. M.; Takado, Yuhei; Comment, Arnaud; Sando, Shinsuke
Abstract: The γ‐glutamyl transpeptidase (GGT) enzyme plays a central role in glutathione homeostasis. Direct detection of GGT activity could provide critical information for the diagnosis of several pathologies. We propose a new molecular probe, γ‐Glu‐[1‐ 13 C]Gly, for monitoring GGT activity in vivo by hyperpolarized (HP) 13 C magnetic resonance (MR). The properties of γ‐Glu‐[1‐ 13 C]Gly are suitable for in vivo HP 13 C metabolic analysis since the chemical shift between γ‐Glu‐[1‐ 13 C]Gly and its metabolic product, [1‐ 13 C]Gly, is large (4.3 ppm) and the T 1 of both compounds is relatively long (30 s and 45 s, respectively, in H2 O at 9.4 T). We also demonstrate that γ‐Glu‐[1‐ 13 C]Gly is highly sensitive to in vivo modulation of GGT activity induced by the inhibitor acivicin. Abstract : See enzymatic reactions in vivo : γ‐Glu‐[1‐ 13 C]Gly was designed as a hyperpolarized NMR probe for monitoring of GGT activity. The properties of this probe, for example, a large chemical shift change and sufficient hyperpolarization lifetime, are suitable for hyperpolarized 13 C metabolic analysis. The designed probe allowed for the first time the real‐time analysis of in vivo GGT activity.